2019
DOI: 10.1093/gigascience/giy162
|View full text |Cite
|
Sign up to set email alerts
|

A near-chromosome-scale genome assembly of the gemsbok (Oryx gazella): an iconic antelope of the Kalahari desert

Abstract: BackgroundThe gemsbok (Oryx gazella) is one of the largest antelopes in Africa. Gemsbok are heterothermic and thus highly adapted to live in the desert, changing their feeding behavior when faced with extreme drought and heat. A high-quality genome sequence of this species will assist efforts to elucidate these and other important traits of gemsbok and facilitate research on conservation efforts.FindingsUsing 180 Gbp of Illumina paired-end and mate-pair reads, a 2.9 Gbp assembly with scaffold N50 of 1.48 Mbp w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The use of Hi‐C data successfully incorporated scaffolds into 29 chromosomes, increasing the scaffold N50 to 100.4 Mb. This is more than 20 times the scaffold N50 reported for the sable antelope (~4.6 Mb, Koepfli et al, 2019) and almost double that of the N50 reported for gemsbok (47 Mb, Farré et al., 2019). In contrast, the contig N50 of the 10X‐Hi‐C assembly was >850 kb which represents a substantial improvement over both sable antelope (45.5 kb) and gemsbok assemblies (17.2 kb).…”
Section: Discussionmentioning
confidence: 58%
“…The use of Hi‐C data successfully incorporated scaffolds into 29 chromosomes, increasing the scaffold N50 to 100.4 Mb. This is more than 20 times the scaffold N50 reported for the sable antelope (~4.6 Mb, Koepfli et al, 2019) and almost double that of the N50 reported for gemsbok (47 Mb, Farré et al., 2019). In contrast, the contig N50 of the 10X‐Hi‐C assembly was >850 kb which represents a substantial improvement over both sable antelope (45.5 kb) and gemsbok assemblies (17.2 kb).…”
Section: Discussionmentioning
confidence: 58%
“…De novo prediction using Augustus 3.2.3 and human gene models resulted in a set of 21,276 candidate protein-coding genes in the sable antelope reference assembly. This quantity is comparable to the 20,892 and 21,426 protein-coding genes found in the domestic cow and Tibetan antelope genomes, respectively, but lower than the 23,125 reference gene set in the gemsbok (Zimin et al 2009; Ge et al 2013; Farré et al 2019). The candidate gene set was then filtered using eggNOG 4.5 orthology data (Huerta-Cepas et al 2016), which reduced the set to 18,828 protein-coding genes.…”
Section: Resultsmentioning
confidence: 58%
“…BUSCO evaluation of gene completeness showed that 3,890 out of 4,104 genes (94.8%) were complete, and only 113 genes (2.7%) were found missing (Table 3). The estimated genome size was 2.926 Gb based on an analysis of k -mer frequency (Marçais and Kingsford 2011), which is comparable to the genome sizes of the domestic cow (2.92 Gb) and the gemsbok (3.2 Gb), another member of the Hippotraginae (Zimin et al 2009; Farré et al 2019).…”
Section: Resultsmentioning
confidence: 79%
“…Alpaca genome assembly was provided by NHGRI sequencing performed at Washington University (Vicugna pacos, GCA_000164845.3, vicPac2). We included the newly sequenced genomes of gemsbok (Oryx gazella) (Farré et al 2019), giraffe (Giraffa camelopardalis), and Indian muntjac (Muntiacus muntjak) (Supplemental Table S1). Although newer assembly versions are available for outgroup human and mouse genomes, using a total of 19 genome assemblies in our work minimized the impact of possible individual misassemblies in these genomes on our reconstructions.…”
Section: Genome Datamentioning
confidence: 99%